Looking inside the tunnelling barrier: I. Strong field ionisation from orbitals with high angular momentum in circularly polarised fields - Kaushal, Jivesh; Smirnova, Olga (Journal of Physics B: Atomic, Molecular and Optical Physics, 2018)
Here and in the two companion papers we use time-dependent analytical R-Matrix (ARM) theory to consider the impact of electron-core interaction on (i) sensitivity of strong field ionisation to the sense of electron rotation in the initial state and (ii) electron spin polarisation. ARM is a rigorous approach to strong field ionisation that takes advantage of the semiclassical nature of electron dynamics in strong laser fields and naturally incorporates complex-valued classical trajectories in the time-propagation. While the appearance of complex time is associated with optical tunnelling, complex coordinates reflect non-adiabaticity of the electron response to the strong laser field. We focus on non-adiabatic electron-core interaction in the sub-barrier region and show how it affects ionisation from orbitals with high angular momentum ℓ = 2, 3 in multiply charged atomic ions with strong electron-core interaction. In this paper we discuss sub-cycle ionisation yields, while in the companion papers we focus on the effects of the long-range core potential on the 'initial conditions' (from the ARM perspective, companion paper II) for the photo electron as it emerges from the classically forbidden region and on the spin polarisation of the ejected electron (companion paper III).
CRIS-Team Scopus Importer:2023-04-20
Keywords: attoclock; circularly polarised fields; electron spin polarisation; ring currents; strong field ionization; sub-cycle Coulomb effects